Electric field applications enhance the electron transfer capacity of dissolved organic matter in sludge compost - Tan, Zhihan (Environmental technology, 2024)
Dissolved organic matter (DOM) plays an important role in heavy metal passivation and organic pollutant degradation owing to its redox ability. The structure and composition of DOM are determinants of redox ability changes during composting. Electric field-assisted aerobic composting (EAAC) has been shown to promote the degradation and humification of organic matter in compost. However, how EAAC affects the redox ability of DOM remains unclear. Hence, electron transfer capacity (ETC) of DOM extracted from EAAC was studied using the electrochemical method. Various spectral methods, such as excitation-emission matrix and ultraviolet and visible spectrophotometry were used to study the relationship of ETC with the compositional and structural changes of DOM. Results indicated that EAAC enhanced ETC of DOM at the later stage of composting, and ETC of DOM extracted from the final EAAC product was 10.4% higher than that of the control group. Spectral and correlation analyses showed that EAAC resulted in structural and compositional changes of DOM, and humification degree, aromatic compounds, molecular weight, and fulvic- and humic-like substance contents were improved in EAAC. This conversion increased ETC of DOM. Results of this study will contribute to the understanding of the redox of DOM and in expanding the application of EAAC products